py360tool: Um Framework para Manipulação de Vídeo 360◦ com Ladrilhos - Garcia, Henrique D.; Carvalho, Marcelo M. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
The streaming of 360◦ videos is one of the most bandwidth-demanding virtual reality (VR) applications, as the video must be encoded in ultra-high resolution to ensure an immersive experience. To optimize its transmission, current approaches partition the spherical video into tiles, which are encoded at different bitrates and selectively delivered, based on the viewing direction of the user (viewport). The complexity of this architecture, which involves viewport prediction, tile selection, bit rate adaptation, and handling of parallel streaming, requires new tools to evaluate quality of experience (QoE) and quality of service (QoS), especially due to its interactive nature and low reproducibility. This work introduces py360tools, a Python library to handle tile-based 360◦ video streaming. The library automates key client-side tasks, such as spherical projection reconstruction, viewport extraction, and tile selection, facilitating the playback and simulation of streaming sessions. Furthermore, py360tools offers a flexible architecture, enabling efficient analysis of different projections and tiling strategies.